Acute Carpal Tunnel Syndrome Secondary to Amyloidosis - Ömer Serdar Hakyemez; Fatih Arslanoğlu; Murat Birinci; Mehmet Akif Çaçan; Adnan Kara (Case Reports in Orthopedics)
Introduction. ACTS secondary to amyloidosis is a very rare situation in the literature, and here, we present a unique case of ACTS secondary to amyloidosis. Case Report. A 61-year-old male patient was admitted to our hospital with complaints of numbness in the lateral half of his 1, 2, 3, and 4 fingers of his right hand. These complaints started acutely, and the patient did not have a history of trauma. His clinical examination was suitable for acute carpal tunnel syndrome. Discussion. Carpal tunnel syndrome, as well as acute carpal tunnel syndrome, may occur based on different causes. ACTS is very rare, especially when it is not caused by a trauma. Here, we presented a unique case of ACTS based on amyloidosis. Conclusion. It should be kept in mind when ACTS may occur in patients with the diagnosis of amyloidosis.